Research book on metaheuristic algorithms and machine learning techniques in energy and power systems - Mohd Herwan, Sulaiman; Zuriani, Mustaffa (Penerbit UMP, 2025)
This research book is a culmination of scholarly work supported by a research grant, aimed at advancing the application of metaheuristic algorithms and machine learning techniques in solving complex problems in energy and power systems. It presents a comprehensive compilation of studies, methodologies, and experimental findings derived from funded research, offering valuable contributions to the field of computational intelligence in energy applications.